1999
DOI: 10.1016/s0378-1097(99)00034-8
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution genomic fingerprinting of Campylobacter jejuni and Campylobacter coli by analysis of amplified fragment length polymorphisms

Abstract: A method for high-resolution genomic fingerprinting of the enteric pathogens Campylobacter jejuni and Campylobacter coli, based on the determination of amplified fragment length polymorphism, is described. The potential of this method for molecular epidemiological studies of these species is evaluated with 50 type, reference, and well-characterised field strains. Amplified fragment length polymorphism fingerprints comprised over 60 bands detected in the size range 35^500 bp. Groups of outbreak strains, replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 11 publications
(30 reference statements)
6
60
0
3
Order By: Relevance
“…Strain 6871 also showed only 94.6 to 96% groEL sequence similarity with C. jejuni, whereas the intraspecies sequence similarities among the other strains ranged from 98 to 100%. Hippurate-negative C. jejuni strains may represent a distinct clonal lineage of C. jejuni, as proposed previously (15).…”
Section: Discussionsupporting
confidence: 61%
“…Strain 6871 also showed only 94.6 to 96% groEL sequence similarity with C. jejuni, whereas the intraspecies sequence similarities among the other strains ranged from 98 to 100%. Hippurate-negative C. jejuni strains may represent a distinct clonal lineage of C. jejuni, as proposed previously (15).…”
Section: Discussionsupporting
confidence: 61%
“…Recently, this method has been adapted for epidemiological typing of C. jejuni and C. coli. These studies demonstrated the subtyping of individual strains, and have already differentiated between two species (Duim et al, , 2000Kokotovic & On, 1999 ;On & Harrington, 2000). In this study, the value of AFLP analysis was determined for the identification and differentiation, at strain level, of nine Campylobacter species and three subspecies belonging to well-defined taxa and representing Campylobacter species that are very important in a veterinary context.…”
Section: Introductionmentioning
confidence: 93%
“…Whole-genome fingerprinting by amplified fragment length polymorphisms (AFLP) is a powerful tool for concurrent taxonomic and subtyping analyses of various bacterial species, and it has been shown to accurately identify interstrain relationships at the subspecies, species, and strain levels (8,14,(23)(24)(25)(26). It has been suggested (23) that the use of AFLP profiling could help resolve the complex taxonomic structure of C. concisus and assess the prevalence of diverse genomospecies isolated from clinical samples, thus elucidating more clearly their potential roles in gastrointestinal illness.…”
mentioning
confidence: 99%